Respiratory symptoms and pulmonary function impairment among textile industry workers in Alexandria, Egypt - Noha Elshaer; Nermin Foda; Sameh Shehata (AOSIS, 2023)
Occupational exposure to cotton dust is still an important cause of respiratory problems in textile workers particularly in less developed countries like Egypt. Evaluate respiratory symptoms and diseases, and pulmonary function pattern among Egyptian textile workers. Cross sectional comparative study was conducted from December 2019 to September 2020 in a textile factory in Egypt; 364 male workers (184 cotton dust exposed workers, and 180 unexposed workers) were included. Participants were subjected to an interviewing questionnaire, British Medical Research Council questionnaire, anthropometric measurements, pulmonary function tests, and byssinosis grading format. Descriptive and analytic statistics were conducted. Chronic cough, phlegm production, and shortness of breath grade I, II and III were more reported in cotton dust exposed workers than unexposed workers (P0.01, P0.01, and P=0.02, respectively). Prevalence of chronic bronchitis was significantly higher among cotton dust exposed workers (12%) than unexposed workers (3.9%)(P0.01). The mean percent predicted values of lung function indices reflecting large-1irway function (VC, FVC, FEV1,FEV1%, PEFR, and FEF75) were significantly lower in cotton dust exposed workers (P0.01). Prevalence of byssinosis was 22.8%. Workers with byssinosis had significantly higher prevalence of respiratory symptoms, chronic bronchitis, cross-shift reduction in PEFR and significant decrease in mean percent predicted values of FVC, FEV1, PEFR, FEF75, and FEF50 than workers without byssinosis. This study revealed a substantial association between cotton dust exposure at work and respiratory symptoms and morbidity. Regular measurement of cross shift change in PEFR is recommended among exposed workers for early diagnosis of byssinosis.